2005
DOI: 10.1016/j.febslet.2005.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Rat limbal epithelial side population cells exhibit a distinct expression of stem cell markers that are lacking in side population cells from the central cornea

Abstract: The side population (SP) phenotype is shared by stem cells in various tissues and species. Here we demonstrate SP cells with Hoechst dye efflux were surprisingly collected from the epithelia of both the rat limbus and central cornea, unlike in human and rabbit eyes. Our results show that rat limbal SP cells have a significantly higher expression of the stem cell markers ABCG2, nestin, and notch 1, compared to central corneal SP cells. Immunohistochemistry also revealed that ABCG2 and the epithelial stem/progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…Although a surface marker for limbal epithelial stem cells has not been defined yet, several methods have been used to isolate stem cells from the limbal epithelium by FACS. Isolation of a side population based on Hoechst33342 dye exclusion that comprised less than 1% of all the cells has been reported by several groups (29,70,76,77,80,111,112). Sorting the side population revealed species specific differences.…”
Section: Isolation Of Lescmentioning
confidence: 93%
See 1 more Smart Citation
“…Although a surface marker for limbal epithelial stem cells has not been defined yet, several methods have been used to isolate stem cells from the limbal epithelium by FACS. Isolation of a side population based on Hoechst33342 dye exclusion that comprised less than 1% of all the cells has been reported by several groups (29,70,76,77,80,111,112). Sorting the side population revealed species specific differences.…”
Section: Isolation Of Lescmentioning
confidence: 93%
“…In rats, a side population could be isolated also from the central cornea in addition to the limbal SP. However, central SP cells neither showed stem cell characteristics, nor were ABCG2 positive, indicating that several types of transporters may take part in Hoechst33342 dye efflux in the rat cornea (111). In addition, the presence of ABCG2 positive, slow cycling Langerhans cells was demonstrated in the limbal basal epithelium of rats, implying that cells sorted based on ABCG2 expression or Hoechst dye exclusion may yield a heterogeneous population of rat limbal stem cells (113).…”
Section: Isolation Of Lescmentioning
confidence: 96%
“…The frequency of SP cells from the freshly isolated limbal epithelium varied from 0.2% to 0.64% in humans and from 0.4% to 1.21% in rabbits, while no SP cells were detected in human and rabbit central corneas. Interestingly, a recent study showed that 4.6% of SP cells are isolated from the rat central corneal epithelium, which is significantly higher than 0.4% from the rat limbus [80]. Future studies are needed to determine whether ABCG2 is expressed not only in the limbal tissue, whether other members of ABC transporter family may be expressed by some corneal cells, and whether cells other than SCs can also express ABCG2.…”
Section: How Can Limbal Epithelial Scs and Their Niche Cells Be Isolamentioning
confidence: 97%
“…Using this method, SP cells have been isolated from human [23][24][25], rat [80], and rabbit [24,81,82] limbal tissues. The frequency of SP cells from the freshly isolated limbal epithelium varied from 0.2% to 0.64% in humans and from 0.4% to 1.21% in rabbits, while no SP cells were detected in human and rabbit central corneas.…”
Section: How Can Limbal Epithelial Scs and Their Niche Cells Be Isolamentioning
confidence: 99%
“…In the mouse model, these limbal stem cells only represent from <1% (Budak et al, 2005) to 3.8% (Krulova et al, 2008) of the limbal cell population. In rat and human cornea, flow cytometry and analysis of certain stem cell markers (such as ABCG2 expression) has shown that these cells range from 0.20% (Watanabe et al, 2004) to 10% (Umemoto et al, 2005) of the total limbal epithelial cell population. The small fraction they represent is important in understanding techniques for extraction and cultivation of stem cells.…”
Section: Stem Cell Localizationmentioning
confidence: 99%